1978
DOI: 10.1172/jci108963
|View full text |Cite
|
Sign up to set email alerts
|

Rat Intestine Secretes Discoid High Density Lipoprotein

Abstract: A B S T R A C T High density lipoprotein was isolated from pooled rat serum and mesenteric lymph of lymph fistula rats. In most experiments, 5,5'-dithionitrobenzoic acid, an inhibitor of the enzyme lecithin:cholesterol acyltransferase, was added during the collection of lymph to prevent modification of the lipid composition of newly secreted lipoproteins. Negative staining electron microscopy of lymph high density lipoprotein revealed discoidal particles (190+3 x 55+1 A) which tended to form rouleaux, smaller … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
77
3

Year Published

1980
1980
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 252 publications
(85 citation statements)
references
References 26 publications
5
77
3
Order By: Relevance
“…10). Early studies involving mesenteric lymph collection (71) and liver perfusion (72) concluded that HDL was produced in these two organs. Tissue-specific knockout experiments will be required to sort out the relative contributions of liver and intestine to HDL production.…”
Section: Discussionmentioning
confidence: 99%
“…10). Early studies involving mesenteric lymph collection (71) and liver perfusion (72) concluded that HDL was produced in these two organs. Tissue-specific knockout experiments will be required to sort out the relative contributions of liver and intestine to HDL production.…”
Section: Discussionmentioning
confidence: 99%
“…We and others found that a human intestinal cell line, CaCo-2, expresses ABCA1 ( 9,10 ) and secretes HDL though the involvement of ABCA1 ( 11 ). Experimental studies with rodents have demonstrated that the liver and small intestine (SI) are the major organs for ABCA1 expression and HDL production (12)(13)(14)(15)(16). Recent fi ndings have shown that, although the overexpression of hepatic ABCA1 in experimental mouse models is not benefi cial ( 17 ), the overexpression of intestinal ABCA1 is benefi cial for atherosclerosis ( 18 ), indicating that HDL from SI may perform unique and distinct functions.…”
Section: Western Blot Analysesmentioning
confidence: 99%
“…HDL fractions from mouse serum, SI lymph perfusate, SI lymph ( 14 ), and liver perfusate ( 28 ) from WT mice were buffer exchanged with 10 mM triethylammonium bicarbonate buffer (Sigma-Aldrich, St. Louis, MO) and concentrated by centrifugation (6,000 g , 30 min at 4°C) using Vivaspin2 (MW 3000; GE Healthcare, Buckinghamshire, UK). The protein concentration of each sample was determined with the Bradford method and adjusted to 7.5 mg/ml.…”
Section: Ms Analysis Of Hdl Fractionsmentioning
confidence: 99%
See 1 more Smart Citation
“…From this it has been concluded that the discoidal particles are nascent high-density lipoproteins and that these precursor lipoproteins are converted to mature circulating high-density lipoproteins by lecithin -cholesterol acyltransferase. The main apolipoprotein of the discoidal lymph high-density lipoproteins is apolipoprotein A-I [34]. On the contrary, in 'nascent' liver high-density lipoproteins, apolipoprotein-E has been described as the main apolipoprotein [9].…”
Section: Discussionmentioning
confidence: 99%